2021
DOI: 10.32802/asmscj.2020.653
|View full text |Cite
|
Sign up to set email alerts
|

Visitors’ Perception of the Effectiveness of Leptospirosis Health Hazard Warning Signage in Recreational Parks, Hulu Langat District, Malaysia

Abstract: This study primarily intends to determine visitors’ perception of leptospirosis health hazard warning signage and its effectiveness within natural recreational parks in the district of Hulu Langat. This cross-sectional study was conducted in four out of seven natural recreational parks, installed with leptospirosis health hazard warning signage. A total of 209 respondents were recruited purposively in this study and completed the questionnaires. Majority of the respondents were male (57.4%), 40 years old and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…EC susceptibility was 67% higher among Malaysian adolescents exposed to tobacco advertisement at the point-of-sale who reported it as attractive, which is in line with a longitudinal study which reported that such exposure predicted susceptibility to EC initiation after 6 months 35 . Through the advertising tactic of the tobacco industry based on hierarchy-of-effects models, the EC advertisement makes the target group aware and develops receptivity toward EC, and finally influences their consumption behavior 36 , 37 . ECs are frequently being marketed as glamorous and healthful to increase curiosity and initiation among youth who never use EC.…”
Section: Discussionmentioning
confidence: 99%
“…EC susceptibility was 67% higher among Malaysian adolescents exposed to tobacco advertisement at the point-of-sale who reported it as attractive, which is in line with a longitudinal study which reported that such exposure predicted susceptibility to EC initiation after 6 months 35 . Through the advertising tactic of the tobacco industry based on hierarchy-of-effects models, the EC advertisement makes the target group aware and develops receptivity toward EC, and finally influences their consumption behavior 36 , 37 . ECs are frequently being marketed as glamorous and healthful to increase curiosity and initiation among youth who never use EC.…”
Section: Discussionmentioning
confidence: 99%